Evaluating the types of osteotomies performed in rhinoplasty - Iyer, Nikita; Patil, Supriya; Pimpalkhute, Ketki; Rajivkumar, Kalpana; Patil, Parag (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Nasal bone osteotomies are essential in rhinoplasty, particularly in the context of India where rhinoplasty is a prevalent aesthetic procedure. These osteotomies serve various purposes, from widening a narrow nasal bony pyramid to correcting deviations or width issues. Beyond routine cases, congenital, traumatic, or developmental deformities may require unique approaches to address nasal bone structure. However, consensus on the optimal osteotomy technique remains elusive. The ideal technique should be precise, reproducible, safe, and minimize postoperative complications like bruising and swelling. This study focuses on identifying the most commonly used osteotomy technique in rhinoplasty that yields favorable results. This retrospective study spanned from January 2021 to July 2023 and included 60 patients undergoing rhinoplasty. Preoperative data were documented, intraoperative methods were recorded, and postoperatively, the prevalence of different osteotomy types was statistically analyzed. Among the 60 patients, 70% (42 patients) underwent combined medial and lateral osteotomies. Within this group, 12 patients had lateral osteotomies using the high-to-high method, 5 patients had the low-to-low method, and 25 patients had the high-to-low lateral osteotomy. This study underscores the critical role of osteotomy in rhinoplasty. A retrospective analysis of 60 rhinoplasty cases revealed that the lateral osteotomy high-to-low method is the most commonly employed technique. This finding suggests that this particular approach is favored by surgeons for its effectiveness in achieving the desired outcomes in rhinoplasty procedures.